Morphological Effect of Vitamin D Deficiency on Globular Substances in Mice. Issue 9 (October 2021) - Song, Penglong; Zhao, Xianshu; Xu, Yanjun; Zhao, Zhigang; Liu, Yang; Gao, Qian
Abstract : Objective: Many authors, including us, elucidated that vitamin D deficiency was a risk factor for benign paroxysmal position vertigo. We speculated vitamin D deficiency was likely to intervene otoconia formation by globular substance (GS). Methods: Kunming mice were randomly divided into three groups: vitamin D sufficient group (12-wk standard control diet), vitamin D deficiency group (16-wk vitamin D deficiency diet), and vitamin D supplement group (16-wk vitamin D deficiency diet and followed 8-wk standard control diet). At 12, 16, and 24 weeks, blood was collected for measuring vitamin D and macula utriculi were obtained for research under scanning electron microscope (SEM). We randomly selected 10 SEM photographs of macula utriculi in each mouse, counted cilium and GS, and measured diameters of counted GS. The ratio of the number of GS to cilium in each SEM photograph was defined as density of GS. Results: The diameter and density of GS were larger and higher in vitamin D deficiency group than sufficient group ( p  < 0.05; p  < 0.05). There was no significant difference in density and diameters of GS between vitamin D deficiency and supplement group. The rough and grainy surface became smoother and smoother along with vitamin D deficiency, and reappeared after vitamin D supplement for 8 weeks. Conclusion: GS secreted as a precursor of mature otoconia is affected by vitamin D deficiency and vitamin D supplementation can mitigate the effects in mice. The density of GS, a quantitative method we designed, can quantify GS well. Abstract : Supplemental Digital Content is available in the text